MIGRANT WORKERS AS A RESOURCE FOR THE DEMOGRAPHIC DEVELOPMENT OF RUSSIA AND THE REPUBLIC OF KAZAKHSTAN - Ryazantsev Sergey Vasilievich (Scientific Journal of Pedagogy and Economics, 2021)
The article discusses the features of the demographic development of Russia and Kazakhstan in modern conditions and the medium term. The scientific problem of the study is to identify the features of the current stage and prospects of demographic development and the contribution of migration to the formation of the population and labor resources of Russia and the Republic of Kazakhstan. It was revealed that Russia and the Republic of Kazakhstan became the two largest countries for the reception of migrants in the Eurasian space. The prerequisites for large-scale and active labor migration to these states are demographic trends, growing labor requirements and the relatively successful economic development of the two countries. The key labor donors for both countries are currently Central Asian states. So, between the countries of the region on the one hand, Russia and the Republic of Kazakhstan, on the other hand, the Eurasian migration corridor has formed, which is currently one of the largest on a global scale. In both countries, it is necessary to strengthen the direction of migration policy associated with attracting labor migrants as a resource for demographic development. Despite the temporary stay in the host countries, many labor migrants pass into the category of permanent residents of Russia and the Republic of Kazakhstan. Russia, as the main host country, has not yet fully benefited from the demographic advantages of the Euro-Asian migration corridor. The country’s migration policy remains quite tough and inadequate in the demographic situation. Although the approach seems to be declared at the state level that migration should be one of the development resources, many obstacles to the integration of migrants, including migrants from Central Asian countries, the main donor region, remain in the system of migration policy itself, in its mechanisms and implementation tools. The Republic of Kazakhstan, although it has not yet encountered the demographic problem in a form like Russia, can already consider labor migration as a resource for future development in pragmatic interests. It is noted that both Russia and the Republic of Kazakhstan, as countries receiving labor migrants, should emphasize in their migration policy the integration of part of labor migrants into the host society.